Analysis of JIBOR Discontinuity: Comparison of Spread Adjustment for Several Alternative Reference Rates for 1-Month JIBOR - Zulfikar, Harly; Taufiq, Afif Amrullah; Giyatno, Among (Persatuan Aktuaris Indonesia, 2025)
The planned discontinuation of the Jakarta Interbank Offered Rate (JIBOR) publication by Bank Indonesia, effective January 1, 2026, has significant implications for the financial industry, particularly for life insurance contracts that reference JIBOR. Therefore, a credible and economically equivalent Alternative Reference Rate is needed. This paper addresses the discontinuity from two perspectives, forecasting methods for accurately predicting JIBOR post-discontinuation and analyzing the transition to four Alternative Reference Rates: Indonesia Overnight Index Average (IndONIA), BI Rate, LPS Rate, and the average deposit rate of state-owned banks (Bank Himbara). The methodology involves historical data analysis over the past five years, following the National Working Group on Benchmark Reform (NWGBR) recommendations. Findings show that for forecasting, the Autoregressive Model with Box-Cox transformation has the smallest error compared to actual JIBOR. Among Alternative Reference Rates, IndONIA has the smallest error compared to actual JIBOR. This paper is expected to provide insights for financial industry stakeholders affected by the JIBOR discontinuity, including insurance products using JIBOR as a Reference Rate in cash value calculations